2017
DOI: 10.12962/j23373520.v6i2.25502
|View full text |Cite
|
Sign up to set email alerts
|

Investigasi Keinginan Konsumen Wanita Membeli Produk Green Skincare dengan Model Pro-Environmental Planned Behavior

Abstract: Masyarakat global saat ini semakin menyadari bahaya dari kerusakan lingkungan, hal itu mempengruhi perilaku konsumen dalam meggunakan produk ramah lingkungan khususnya pada produk kecantikan. The Body Shop dan Sariayu Martha Tilaar merupakan perusahaan kecantikan yang telah menerapkan green concept di Indonesia. Produk skincare dipilih sebagai objek amatan karena banyak masyarakat di Indonesia yang menggunakannya dibanding dengan varian produk kecantikan lainnya, namun penelitian mengenai minat beli green skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The results showed that the most significant factor that affects behavioral intention (BI) in both Taiwan and Indonesia is attitude (AT). The factors of the Pro-Environmental Planned Behavior (PEPB) model that influence people to purchase green skincare products were also found in a study by Puspita et al [40]. The study results show that perceived authority support and perceived environmental concern positively affect attitude, subjective norms, and perceived behavioral control, all of which can positively affect the desire to buy green skincare products.…”
Section: Pro-environmental Planned Behavior Modelsupporting
confidence: 62%
See 1 more Smart Citation
“…The results showed that the most significant factor that affects behavioral intention (BI) in both Taiwan and Indonesia is attitude (AT). The factors of the Pro-Environmental Planned Behavior (PEPB) model that influence people to purchase green skincare products were also found in a study by Puspita et al [40]. The study results show that perceived authority support and perceived environmental concern positively affect attitude, subjective norms, and perceived behavioral control, all of which can positively affect the desire to buy green skincare products.…”
Section: Pro-environmental Planned Behavior Modelsupporting
confidence: 62%
“…The present study's theoretical framework is based on Pro-Environmental Planned Behavior (PEPB) used in prior studies [38][39][40][41][42] to predict Filipinos' acceptance of renewable energy sources. Consumers' intention to behave pro-environmentally is the primary predictor of such behavior, and various researchers have explored this link [43][44][45].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous studies have established a significant relationship between subjective norms and behavioural intention. For example, subjective norms have been proven positively influence the behavioural intention of environmental impact assessment participation (Persada, 2016), and green skincare purchasing behaviour (Puspita, 2017). Research also revealed that Soliman, 2019), particularly when it comes to consumer's intentions towards remanufactured components (Kumar, 2017;Ma et al, 2017;Pisitsankkhakarn and Vassanadumrongdee, 2020;Wang et al, 2020;Zhu et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This condition can be seen from the selection of various kinds of green products (goods and services) which are not only concerned with the environment, but also become part of efforts to support the realization of the go green movement. Consumer awareness in determining and being more critical in choosing a product, by considering what ingredients are used listed on the organic label before they buy (Puspita et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This illustrates that there is already a desire or interest in the community in using green products. Interest in green products is based on consideration of the existence of an organic label on the product (Puspita et al, 2017). In addition, the level of understanding of green products is inseparable from the company's efforts to influence consumers' desire to have green products that are environmentally friendly (Okada, 2010).…”
Section: Introductionmentioning
confidence: 99%